Socio-spatial disparities in urban green space accessibility: The existing challenge for Toronto in its aspiration to be a liveable city - Dong, Ziyue; Miller, Eric (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2024)
Toronto, a thriving multicultural metropolis, aspires to create an inclusive and livable urban environment meeting diverse resident needs. However, challenges arise due to the uneven distribution of urban green spaces. This study employs a gravity model and Gaussian-based 2SFCA model to assess green space accessibility in Toronto’s dissemination areas. A Gini index and local bivariate Moran’s I illuminate socio-spatial disparities, while Geographically Weighted Regression unveils economic inequalities by correlating green space accessibility with housing prices and their five-year growth. Findings expose stark environmental inequity, with the bottom 20% accessing a mere 7% of spaces and the top 20% enjoying 40%. City center and low-income peri-central areas exhibit pronounced disparities, driven by limited green spaces and intense competition. In flourishing, dense areas, residents pay more for increased green space share, while less-dense areas with ample green spaces see higher housing prices where accessibility prevails. Neighborhoods with abundant green spaces and amenities, notably special school programs, attract families, correlating housing price growth with green space accessibility. Considering diverse district development phases and priorities and potential conflicts, tailored strategies for equitable green space systems are recommended citywide.